1990
DOI: 10.1007/bf00294617
|View full text |Cite
|
Sign up to set email alerts
|

Type C retroviral expression in spontaneous feline olfactory neuroblastomas

Abstract: Three cases of spontaneous olfactory neuroblastoma (ONB) in domestic cats were morphologically and immunocytochemically characterized. Diagnostic light microscopic features included Flexner and Homer-Wright rosettes, while ultrastructurally the cells had neuritic processes, intracellular intermediate filaments, and intercellular junctions. Immunocytochemically, the tumors stained positively for neuron-specific enolase, cytokeratins, and S-100 protein antigens. In each case, a key finding was the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
1
28
0
3
Order By: Relevance
“…SCHRENZEL et al (1990) identified viral particles in three cats with olfactory neuroblastoma that, through IHC, demonstrated an immunoreaction in the cytoplasm of neoplastic cells for FeLV, similar to what was observed in our case. The mechanism by which the virus causes neuroblastoma development has not yet been elucidated (SCHRENZEL et al, 1990). However, the detection of viral particles in neoplastic cells indicated a possible role of FeLV in the origin of these tumors.…”
Section: Neuronalsupporting
confidence: 86%
“…SCHRENZEL et al (1990) identified viral particles in three cats with olfactory neuroblastoma that, through IHC, demonstrated an immunoreaction in the cytoplasm of neoplastic cells for FeLV, similar to what was observed in our case. The mechanism by which the virus causes neuroblastoma development has not yet been elucidated (SCHRENZEL et al, 1990). However, the detection of viral particles in neoplastic cells indicated a possible role of FeLV in the origin of these tumors.…”
Section: Neuronalsupporting
confidence: 86%
“…These were supplemented by another 19 relevant publications found in references cited. 4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The studies were divided into three types, according to their principal objectives: origin and aetiology of ENB, 9,11,15,[17][18][19]21,24,[27][28][29][30][31][32][33][34][35][36][37][38][39][40] histopathological diagnosis; 10,[12][13][14]23,37,[41][42][43][44]…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Since the cranial vault and nasopharynx were severely involved with tumor in Case 1, there is a possibility that neoplastic cells were derived from olfactory sensory cells called as olfactory neuroblastoma [1,4,14,17]. However, the distribution of the tumor mass in Case 1 is quite different.…”
Section: Immunohistochemistorymentioning
confidence: 99%
“…In general, neuroblastomas including medulloblastomas in the central nervous system, are very rare in domestic animals [6]. In the peripheral nervous system, few cases of neuroblastomas in the adrenal medulla, sympathetic ganglia, or nasal cavity (aesthesioneuroblastomas) have been reported in several animal species [1,3,4,6,11,14]. Cordy [3] reported that peripheral neuroblastomas analogous to human in situ neuroblastomas, were often found in adult slaughter cattle and malignant neuroblastomas were seen in premature or stillborn calves and in dogs of all ages [6].…”
mentioning
confidence: 99%